Biograpic research in artists – a researcher’s reflections (Biograficzne badania nad twórczością. Teoria i empiria, 2016)
In her article, the Author presents her reflections and deliberations concerning biographic research, which were the aftermath of interviews that she had carried out among artists. She shares her suggestions on the narrative interviews and the limitations that may appear in the process of reconstructing a biography. She also draws attention to the role of art in these biographies, treating it as an important aspect of life of the studied individuals, but also as a significant element of a reconstructed biography.